Perbandingan Motivasi Belajar Mahasiswa dalam Pembelajaran Daring dan Luring - Ismi Fajariah; Mirda Diah Jayani Amiruddin; Noor Izzati Pratiwi; Saiyidah Mahtari (Universitas Batanghari Jambi, 2023)
The purpose of this research is to find out the comparison of student learning motivation in online and offline learning. The method used is the questionnaire method which contains questions on student motivation with a total of 91 students majoring in Mathematics and Natural Sciences Education semester 5 who study at Lambung Mangkurat University. Questionnaires were analyzed using descriptive analysis with the Rasch model technique. The results showed that the instrument had a Cronbach alpha value of 0.85 with a high degree of reliability. It was concluded that student learning motivation was higher during offline learning than online learning.